PERAN AKTIF PEREMPUAN PENGRAJIN EMPING MELINJO DALAM PENINGKATKAN PENDAPATAN KELUARGA DI DESA WATES KECAMATAN WATES KABUPATEN BLITAR - Efa Fauzi; Tri Kurniastuti; Lintar Brillian P (grafting, 2021)
This study aims to determine the role, analyze the income and contribution of women melinjo chip craftsmen in Wates district in the home industry of melinjo chips. The study used a mixed method and gender analysis of the Harvard model, while for the determination of sampling using the purposive sampling method. The role of women farmers in the hamlet of Wates as housewives and helping to earn extra income as craftsmen emping melinjo. The average income received by the family per month is Rp. 3,000,000. The average monthly expenditure is IDR 1,200,000. So that the average net income per month is IDR 1,800,000. The contribution of women's income to family income is 50%, so women in Wates hamlet contribute quite a lot to the income of farmer families.